2021
DOI: 10.3390/membranes11120991
|View full text |Cite
|
Sign up to set email alerts
|

Separation Iron(III)-Manganese(II) via Supported Liquid Membrane Technology in the Treatment of Spent Alkaline Batteries

Abstract: In this paper, the transport of iron(III) from iron(III)-manganese(II)-hydrochloric acid mixed solutions, coming from the treatment of spent alkaline batteries through a flat-sheet supported liquid membrane, is investigated (the carrier phase being of Cyanex 923 (commercially available phosphine oxide extractant) dissolved in Solvesso 100 (commercially available diluent)). Iron(III) transport is studied as a function of hydrodynamic conditions, the concentration of manganese and HCl in the feed phase, and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The characteristics of both membranes are mentioned in the previous section. The use of PVDF as support for liquid membrane has been reported by various research studies for the separation, recovery, and extraction of different chemicals [17,18,30].…”
Section: Effect Of Membrane Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of both membranes are mentioned in the previous section. The use of PVDF as support for liquid membrane has been reported by various research studies for the separation, recovery, and extraction of different chemicals [17,18,30].…”
Section: Effect Of Membrane Supportmentioning
confidence: 99%
“…SLMs have been extensively used for the recovery of metals from industrial process streams. Several authors have reported the recovery of metal and anions such as copper, zinc, nickel, Cr (VI), Hg, and cadmium through liquid membrane contactors [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with solvent extraction, selective recovery of metal ions can be achieved through use of suitable extractant and manipulating chemistry of feed and stripping phases [ 7 , 8 , 10 ]. In many SLM studies, which involved recovering copper, chelating oxime extractants were found to transport copper preferably over other metal ions [ 11 , 12 , 13 ], whereas solvating extractants such as Cyanex 923 were succesful in transporting metals that assumed metal-salt forms in aqueous feed [ 14 , 15 ]. Some studies employed ionic liquids with tailorable chemical structure to facilitate transport of target metal ions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional chemical techniques for trace metal control include precipitation, ion exchange [7], electrocoagulation [8], membrane separation [9], reverse osmosis [10], electrodialysis [11], solvent extraction [12], phytoextraction [13], ultrafiltration [14], adsorption, etc. [15][16][17].…”
Section: Introductionmentioning
confidence: 99%